Fostering Contextual and Collaborative Learning: Integrating Learning Resources and Interactive Media in Social Studies Classrooms - Hidayat, Hikmalyansyah (Perspektif Pendidikan dan Keguruan, 2025)
This study aims to describe the integration of various learning resources and interactive media in Social Studies (IPS) instruction for grades 7A and 9B, particularly during post-noon sessions often marked by student fatigue and declining focus. Employing a qualitative descriptive method rooted in field-based teaching experience, data were gathered through reflective journals, direct classroom observations, and instructional documentation. Strategies such as Wordwall, Crossword Puzzles, and Snowball Throwing were implemented to foster engaging, collaborative, and meaningful learning experiences. The findings reveal that such media integration significantly enhances students’ cognitive, affective, and psychomotor engagement. Wordwall served as a fun and competitive assessment tool, Crossword Puzzles encouraged group problem-solving and discussion, while Snowball Throwing broke classroom rigidity and inspired spontaneous participation. These results underscore that effective teaching is not merely about delivering content but designing learning that resonates with students’ realities. This field-based reflection shows that when teachers thoughtfully combine resources, technology, and contextual strategies, classroom challenges can be transformed into learning opportunities. Therefore, this study implies that adaptive media integration is essential to sustain student motivation and offers a valuable direction for future research in interactive learning strategies, especially within dynamic classroom environments.